Optimizing Employee Loyalty Through Career Development, Work Life Balance, and Compensation - Walidah, Laili Zana; Andriani, Dewi; Kusuma, Kumara Adji (Jurnal Ilmu Manajemen Advantage, 2024)
This research aims to determine the influence of career development, work life balance and compensation on the loyalty of Wonoayu Community Health Center employees, both partially and simultaneously. This research is a type of quantitative research using a 1-5 Likert scale analysis tool and data testing, namely validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, and hypothesis testing. The data collection technique uses a questionnaire distributed via a Google form link. The population in this study was Wonoayu Community Health Center employees, totaling 95 people and the sampling technique used a census technique, namely 95 respondents. The results of this research prove that the loyalty of Wonoayu Community Health Center employees can be influenced through career development, work-life balance and compensation. From the results of the coefficient of determination, it is known that the contribution of career development, work-life balance and compensation variables has an influence on the employee loyalty variable, namely 78.7% and the remaining 21.3% is influenced by other variables not used in this research.